ANALISIS TINGKAT OPTIMIS, PESIMIS DAN EKSPEKTASI PENGEMBALIAN TERHADAP PERILAKU INVESTOR PADA INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA - Bayu Laksma Pradana; Andreas Kiky (STIE Wiyatamandala, 2017)
Human decision making process can be very complicated and complex. Especially in case of financial decision making by the investor in Financial Market. Rational investor should be risk averse and make some investment decision based on the risk and return (or reward) that could be obtained from the asset. But most of these “rational investors’ are failed to be rational investor. Many of them make some decision just base on heuristic judgment and lead them to bias or error. Some bias or errors are very common to be found, especially when we used system 1 in our decision making process. We tend to be fooled by past experience or if we could link with financial decision making is the past data. Our research aim to find the behavioral pattern that could be found in trading volume. We suspect there is some irrational decision making that might be happen in Jakarta Stock Exchange. We examine IHSG value and its volume from 2014 to 2016. Result from this research is far from expectation. R2 value is very low (about 2.3%) and other t-test only showed 1 dependent variable is significant. On the next step in behavioral study we think need to change the sample and applied this model on specific stocks price not on index. And after this research we also start to make behavior research roadmap to investigate risk preference base on behavior study that has been conducted by Thaler (2016), Ariely (2010) or Kahneman (2013).